PROJECT-ORIENTED TEACHING OF POWER ELECTRONICS DURING UNDERGRADUATE STUDY - Mihalič Franc; Milanovič Miro; Hren Alenka (Journal of Energy Technology, 2024)
This paper presents the results and acquired experience from the Project-Oriented Teaching (POT) of the undergraduate students in Power Electronics course at the Faculty of Electrical Engineering and Computer Science in Maribor, based on using a boost converter test-board. In the project task, the students are asked to calculate the main boost converter circuit parameters capacitor C and inductor L; they are additionally required to design the inductor L in order to meet the project goals. The whole project design is based on the ideas from the CDIO (Conceive, Design, Implement, Operate) framework in which the students are encouraged to consider the whole system process to obtain hands-on experience. Finally, students have to design a PI-voltage controller to connect their newly obtained knowledge with their prior knowledge.